Didactic Opportunities of Information-Communication Technologies in the Control of Physical Education - Koryahin, Victor; Mykytyuk, Zinovy; Blavt, Oksana; Dolnikova, Liubov; Stadnyk, Volodymyr (Physical Education Theory and Methodology, 2020)
The study objective is to justify and implement information and communication technologies in the test control of the development level of the frequency of movements, as a manifestation of speed qualities in the process of physical education. Materials and Methods. To solve the research tasks, the study used the methods of comparing and contrasting, analysis, synthesis, abstraction, formalization and technical modeling. Results. An electronic device for the exercise controlling the movement frequency of the hands to evaluate speed qualities was developed for the research purpose. The device is designed on the basis of capacitive type proximity sensors. The signal received by the sensors is processed in the microcontroller unit during the test and transmitted to the personal computer via the communication interface. On a personal computer, using the developed software, they control the time of completion of the test task. Conclusions. The developed information and communication technologies based on electronic monitoring device embodies a new approach to addressing the challenge of improving the performance of speed control in physical education by ensuring that objective and reliable test data are obtained promptly.